Natural conditions for the development of lake tourism in Poland - Skowron, Rajmund (Bulletin of Geography. Physical Geography Series, 2023)
There are about 6,800 lakes in the Polish Lowlands. They are a potential place for rest and recreation not only for the local population, but also for those coming from other regions of Poland and foreign guests. The work was based on the analysis of water temperature data in lakes in the years 1961–2020. The highest surface water temperatures in lakes occurred most often at the turn of the last decade of July and the fi rst decade of August, reaching values above 2 °C in most lakes. In the daily cycle, the highest water temperatures in the surface water layer (up to 1.5 m deep) were recorded mostly between 14:00 and 17:00 (13:00–16:00 GMT). The beginning of the bathing season on lakes in Poland usually falls between May 20 and 25, while the end is in the second half of September, reaching an average of about 69 days, characterized by a positive trend in its duration. According to the Chief Sanitary Inspectorate in Poland, in 2020 there were 602 active bathing areas, most of which were organized on lakes.